Managing Innovation: Are Project Management MethodsEnemies or Allies - Ćirić, Danijela; Lalić, Bojan; Gračanin, Danijela (International Journal of Industrial Engineering and Management, 2016)
To achieve the long-term competitiveness companies are invited to a continuous process of innovation. When talking about innovation we are dealing with opportunities that offer the promise of new growth platforms. This high impact level comes with a set of challenges which lead us to the question how to build innovation capability and make these processes more manageable. Innovations are today mostly implemented through projects that require divergent thinking, willingness to devote resources to projects which are likely to fail and these seem incompatible with project management thinking involving the enforcement of strict standards most corporate cultures embrace. To address this problem, the paper examines whether project management methods are obstacles and constraints or can be used to make this process be more reliable instead of high-risk varied attempts of trial-and error. It is shown that it is of utmost importance to find the best fit between innovation project characteristics and project management approach. An overview of the state of the art about this matter is given. Article history: Received (08.04.2015); Revised (28.10.2015); Accepted (10.02.2016)